Pathophysiology of Antiphospholipid Syndrome - Green, David (Thrombosis and Haemostasis, 2022)
The antiphospholipid syndrome is characterized by antibodies directed against phospholipid-binding proteins and phospholipids attached to cell membrane receptors, mitochondria, oxidized lipoproteins, and activated complement components. When antibodies bind to these complex antigens, cells are activated and the coagulation and complement cascades are triggered, culminating in thrombotic events and pregnancy morbidity that further define the syndrome. The phospholipid-binding proteins most often involved are annexins II and V, β2-glycoprotein I, prothrombin, and cardiolipin. A distinguishing feature of the antiphospholipid syndrome is the “lupus anticoagulant.” This is not a single entity but rather a family of antibodies directed against complex antigens consisting of β2-glycoprotein I and/or prothrombin bound to an anionic phospholipid. Although these antibodies prolong in vitro clotting times by competing with clotting factors for phospholipid binding sites, they are not associated with clinical bleeding. Rather, they are thrombogenic because they augment thrombin production in vivo by concentrating prothrombin on phospholipid surfaces. Other antiphospholipid antibodies decrease the clot-inhibitory properties of the endothelium and enhance platelet adherence and aggregation. Some are atherogenic because they increase lipid peroxidation by reducing paraoxonase activity, and others impair fetal nutrition by diminishing placental antithrombotic and fibrinolytic activity. This plethora of destructive autoantibodies is currently managed with immunomodulatory agents, but new approaches to treatment might include vaccines against specific autoantigens, blocking the antibodies generated by exposure to cytoplasmic DNA, and selective targeting of aberrant B-cells to reduce or eliminate autoantibody production.
Keywords: antiphospholipid antibodies; phospholipid-binding proteins; lupus anticoagulant